2016
DOI: 10.3758/s13414-016-1098-3
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up and top-down attentional contributions to the size congruity effect

Abstract: The size congruity effect refers to the interaction between the numerical and physical (i.e., font) sizes of digits in a numerical (or physical) magnitude selection task. Although various accounts of the size congruity effect have attributed this interaction to either an early representational stage or a late decision stage, only Risko, Maloney, and Fugelsang (Attention, Perception, & Psychophysics, 75, 1137-1147) have asserted a central role for attention. In the present study, we used a visual search paradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 41 publications
(77 reference statements)
10
31
0
Order By: Relevance
“…This interpretation of the data would be consistent with previous research indicating that initiation time and reach curvature originate from two dissociable processes (e.g., Erb, Moher, Sobel, & Song, 2016;Ruitenberg et al, 2016;Strauss, Woodgate, Sami, & Heinke, 2015). Specifically, it is thought that initiation times might be driven by an early action planning stage that is tied to cue-related encoding processes, whereas MT and AUC might reflect mainly top-down (controlled) processes which provide for revision and correction of the decision during the movement execution phase (e.g., Faulkenberry et al, 2016;Sobel, Puri, & Faulkenberry, 2016;Sobel, Puri, Faulkenberry, & Dague, 2017). All together, our analysis of movement dynamics echoes and extends the results obtained using the traditional keypress paradigm in Experiment 1.…”
Section: Discussionsupporting
confidence: 90%
“…This interpretation of the data would be consistent with previous research indicating that initiation time and reach curvature originate from two dissociable processes (e.g., Erb, Moher, Sobel, & Song, 2016;Ruitenberg et al, 2016;Strauss, Woodgate, Sami, & Heinke, 2015). Specifically, it is thought that initiation times might be driven by an early action planning stage that is tied to cue-related encoding processes, whereas MT and AUC might reflect mainly top-down (controlled) processes which provide for revision and correction of the decision during the movement execution phase (e.g., Faulkenberry et al, 2016;Sobel, Puri, & Faulkenberry, 2016;Sobel, Puri, Faulkenberry, & Dague, 2017). All together, our analysis of movement dynamics echoes and extends the results obtained using the traditional keypress paradigm in Experiment 1.…”
Section: Discussionsupporting
confidence: 90%
“…This interpretation of the data would be consistent with previous research indicating that initiation time and reach curvature originate from two dissociable processes (e.g., Erb, Moher, Sobel, & Song, 2016;Ruitenberg et al, 2016;Strauss, Woodgate, Sami, & Heinke, 2015). Specifically, it is thought that initiation times might be driven by an early action planning stage that is tied to cue-related encoding processes, whereas MT and AUC might reflect mainly top-down (controlled) processes which provide for revision and correction of the decision during the movement execution phase (e.g., Faulkenberry et al, 2016;Sobel, Puri, & Faulkenberry, 2016;Sobel, Puri, Faulkenberry, & Dague, 2017). All together, our analysis of movement dynamics echoes and extends the results obtained using the traditional keypress paradigm in Experiment 1.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not currently clear whether format additionally affects the later processes involved in responding. Several recent studies have indicated that manipulations of number encoding can feed forward into the response phase, at least in simple number decision tasks (e.g., Santens and Verguts, 2011; Faulkenberry et al, 2016; Sobel et al, 2016, 2017). As such, the third option remains viable; hopefully future studies can further address the effects of format on response processes in mental arithmetic.…”
Section: Discussionmentioning
confidence: 99%